2022
DOI: 10.1112/blms.12697
|View full text |Cite
|
Sign up to set email alerts
|

Parabolic subgroups of two‐dimensional Artin groups and systolic‐by‐function complexes

Abstract: We extend previous results by Cumplido, Martin and Vaskou on parabolic subgroups of large-type Artin groups to a broader family of two-dimensional Artin groups. In particular, we prove that an arbitrary intersection of parabolic subgroups of a (2,2)-free twodimensional Artin group is itself a parabolic subgroup.An Artin group is (2,2)-free if its defining graph does not have two consecutive edges labeled by 2. As a consequence of this result, we solve the conjugacy stability problem for this family by applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Remark 4. After the first preprint of this paper, [3] generalised the results in Cumplido et al [10] and showed that the intersection of parabolic subgroups is a parabolic subgroup for two-dimensional Artin groups with a Coxeter graph-see next section-in which every vertex is disconnected from at most one other vertex. This completed the set of three hypotheses needed in Theorem A and allowed him two apply Algorithm 4 of Sect.…”
Section: Theorem B Let a Be An Fc-type Artin Groupmentioning
confidence: 69%
“…Remark 4. After the first preprint of this paper, [3] generalised the results in Cumplido et al [10] and showed that the intersection of parabolic subgroups is a parabolic subgroup for two-dimensional Artin groups with a Coxeter graph-see next section-in which every vertex is disconnected from at most one other vertex. This completed the set of three hypotheses needed in Theorem A and allowed him two apply Algorithm 4 of Sect.…”
Section: Theorem B Let a Be An Fc-type Artin Groupmentioning
confidence: 69%
“…1. if G Γ is of spherical type (see [4]), 2. if G Γ is of FC-type and P 1 is of spherical type (see [11] which generalizes [12] where the result was obtained when both P 1 and P 2 are of spherical type), 3. if G Γ is of large type, that is m({u, v}) ≥ 3 for all {u, v} ∈ E (see [5]), 4.…”
Section: Introductionmentioning
confidence: 86%
“…if G Γ is a (2,2)-free two-dimensional Artin group, i.e. Γ does not have two consecutive edges labelled by 2 and the geometric dimension of G Γ is two [3],…”
Section: Introductionmentioning
confidence: 99%
“…Following the release of this paper, Blufstein generalised this approach to a larger class of two-dimensional Artin groups [ 2 ].…”
Section: Intersection Of Parabolic Subgroupsmentioning
confidence: 99%